Ultrasound-Assisted Optimal Development and Characterization of Stevia-Sweetened Functional Beverage - Muhammad Kamran Khan; Muhammad Naveed Asif; Muhammad Haseeb Ahmad; Muhammad Imran; Muhammad Sajid Arshad; Sadia Hassan; Muhammad Imran Khan; Mahr-un Nisa; Muhammad Mohsin Iqbal; Niaz Muhammad (Journal of Food Quality)
Nowadays, blend of different fruit juices as functional beverages is highly recommended to retain maximum concentration of nutrients due to their integrated effect against processing, to utilize underconsumed fruits and/or vegetables, and to provide healthy product to the consumer. The novelty in this particular work is optimization of blend using stevia-based low caloric extract as sweetener to replace high caloric sugar contents. For this purpose, juices of apple and carrot along with the extract of stevia leaves underwent the process optimization using a statistical approach of D-optimal mixture design. The best beverage formulation with high sensory scores was composed of apple juice 70%, carrot juice 27%, and stevia extract (5 g/100 ml) 3%. The optimized beverage was then processed with conventional pasteurization at 95°C for 1 min and compared with ultrasound processing for 15 min at four different amplitudes (20%, 40%, 60%, and 80%). According to the observation, the treatment US60 (60% amplitude for 15 min) showed better retention for total phenolic content (78.65 ± 1.37 mg GAE/100 mL), total flavonoid content (23.53 ± 0.15 mg CE/100 mL), DPPH (66.43 ± 1.45 %), and FRAP (65.17 ± 1.10 mmol Trolox/100 mL) as compared to pasteurized and control samples while keeping other physicochemical properties in range. The research therefore indicates that ultrasound is good alternative to pasteurization and stevia to sugar in terms of functional beverage development.